Does the age of acute care physicians impact their (1) crisis management performance and (2) learning after simulation-based education? A protocol for a multicentre prospective cohort study in Toronto and Ottawa, Canada. Issue 4 (21st April 2018) - Alam, Fahad; LeBlanc, Vicki R; Baxter, Alan; Tarshis, Jordan; Piquette, Dominique; Gu, Yuqi; Filipkowska, Caroline; Krywenky, Ashley; Kester-Greene, Nicole; Cardinal, Pierre; Au, Shelly; Lam, Sandy; et al.
Abstract : Introduction: The proportion of older acute care physicians (ACPs) has been steadily increasing. Ageing is associated with physiological changes and prospective research investigating how such age-related physiological changes affect clinical performance, including crisis resource management (CRM) skills, is lacking. There is a gap in the literature on whether physician's age influences baseline CRM performance and also learning from simulation. We aim to investigate whether ageing is associated with baseline CRM skills of ACPs (emergency, critical care and anaesthesia) using simulated crisis scenarios and to assess whether ageing influences learning from simulation-based education. Methods and analysis: This is a prospective cohort multicentre study recruiting ACPs from the Universities of Toronto and Ottawa, Canada. Each participant will manage an advanced cardiovascular life support crisis-simulated scenario (pretest) and then be debriefed on their CRM skills. They will then manage another simulated crisis scenario (immediate post-test). Three months after, participants will return to manage a third simulated crisis scenario (retention post-test). The relationship between biological age and chronological age will be assessed by measuring the participants CRM skills and their ability to learn from high-fidelity simulation. Ethics and dissemination: This protocol was approved by Sunnybrook Health Sciences Centre Research Ethics Board (REB Number 140–2015) and the Ottawa Health Science Network Research Ethics Board (#20150173–01H). The results will be disseminated in a peer-reviewed journal and at scientific meetings. Trial registration number: NCT02683447; Pre-results .